A comparison of equivalent static (Indonesian code) and dynamic analysis on multistorey reinforced concrete building frames - Widodo
This study attempts to investigate the application of the dynamic analysis method in multi-storey reinforced concrete buildings using different sets of applied earthquake ground accelerations and then, to compare the results with the Indonesian Building Code provision. Particularly the study seeks to determine the floor lateral forces of multi-storey buildings for different earthquake ground acceleration. The study is limited to the elastic response and the maximum floor to floor horizontal displacement allowed by the Indonesian Building Code.
Modal analysis or modal superposition method is used in reducing the multi-degree of freedom system to a set of single-degree of freedom system of equations. For numerical integration, the constant velocity method is used. Available earthquake records are utilized to provide the forcing function.
In general the results of the study indicate that the floor horizontal forces caused by different earthquake ground acceleration (e.g., El Centro N-S, Taft, and El Centro N-90-W) are very different from each other. Floor horizontal forces caused by these earthquakes are always greater thatn the equivalent static floor horizontal force of the code. Meanwhile +/- 1/3 of El Centro N-S and full scale of Montana earthquakes give floor horizontal forces roughly equivalent to static floor horizontal force of the Indonesian Building Code.
In order to limit the too many possible values of floor horizontal forces, it is necessary to make the following considerations: A. Limit the range of the values of damping ratio as determined by experiment or by theory. B. Specify the rational in limiting the range of allowable floor horizontal displacement. C. Suggest the scale to be used on available earthquake recording to adapt the most possible local earthquake.
Thesis (M.S. Civil Engineering)--University of the Philippines Diliman.
Typescript.
Keywords: Earthquakes and building; Building -- Earthquake effects; Materials -- Dynamic testing